Sub-arc Mantle Heterogeneity of the Northern Luzon Volcanic Arc: Mineral and Whole Rock Compositional Variability in Mantle Xenoliths from Lutao Island - Shellnutt, J Gregory; Yeh, Meng-Wan; Lee, Tung-Yi; Iizuka, Yoshiyuki; Chen, Wei-Yu; Prasanth, M P Manu (Journal of petrology, 2024)
Mantle xenoliths hosted in volcanic rocks from the island of Lutao offer a glimpse into the nature of the mantle beneath the northern Luzon volcanic arc. The xenoliths are spinel-bearing and composed mostly of harzburgite with one lherzolite and one olivine orthopyroxenite. The olivine (Fo92.5–88.9), orthopyroxene (Mg# = 94.6–89.2), and clinopyroxene (Wo49.1–38.1En57.0–45.4Fs3.0–11.0) compositions are similar to those of abyssal peridotites. The spinel compositions are variable and can be principally divided into high-Al (Cr# < 45) and low-Al (Cr# > 45) groupings. The whole rock compositions are similar to abyssal peridotite (Al2O3 = 0.95–2.07 wt %; Mg# = 88.5–90.9) and have U-shaped chondrite normalized rare earth element patterns. The Sr-Nd isotopes of the xenoliths are broadly chondritic (87Sr/86Sri = 0.704400–0.707908; εNd(t) = 0.0 − +1.5). The two-pyroxene equilibrium temperatures range from 900 to 1200 °C with the majority of temperature estimates >1000 °C. The olivine-orthopyroxene-spinel oxygen barometry estimates yielded ΔFMQ values from 0 to +2 and correspond to moderately oxidizing to oxidizing conditions. The xenoliths are likely derived from the Philippine Sea Plate lithospheric mantle that was modified by melt extraction and/or fluid enrichment processes. Trace element and isotopic mixing modeling indicate that 1–2% contamination by subducted South China Sea sediment can explain the Sr-Nd isotopic enrichment and Th and U elemental variability within the xenoliths assuming an initial composition similar to enriched depleted mid-ocean ridge mantle (E-DMM). The anomalously high two-pyroxene equilibrium temperatures of the Lutao xenoliths relative to other regions of the northern Luzon volcanic arc (Iraya <1000 °C) indicate that they were affected by a high-temperature event that was likely a consequence of recent intra-arc rifting that occurred after collision (<6 Ma) between the Luzon arc and the Eurasian margin.